Current progress with serological assays for exotic emerging / re-emerging viruses - Mather, Stuart; Scott, Simon; Temperton, Nigel; Wright, Edward; King, Barnabas; Daly, Janet (2013)
Recent decades have witnessed an unprecedented rise in the outbreak occurrence of infectious and primarily zoonotic viruses. Contributing factors to this phenomenon include heightened global connectivity via air travel and international trade links, as well as man-made environmental alterations, such as deforestation and climate change, which all serve to bring humans into closer contact with animal reservoirs and alter the habitat of vectors, thus facilitating the transmission of viruses between species. Serological assays are integral to tracking the epidemiological spread of a virus and evaluating mass vaccination programs by quantifying neutralizing antibody responses raised against antigenic epitopes on the viral surface. However, conventional serological tests are somewhat marred by equipment and reagent costs, the necessity for high-containment laboratories for studying many emerging viruses, and interlaboratory variability, among other issues. This review details ‘next-generation’ assays aimed at addressing some of the persistent problems with viral serology, focusing on how manipulating the genomes of RNA viruses can produce attenuated or chimeric viruses that can be exploited as surrogate viruses in neutralization assays. Despite the undoubted promise of such novel serological platforms, it must be remembered that these assays have to withstand rigorous validation and standardization measures before they can play an integral role in curtailing the severity of future emerging virus outbreaks.